Evaluasi Kombinasi Infusa Daun Sirih (Piper betle L.) dan Infusa Rimpang Jahe (Zingiber officinale-Roscoe) terhadap Tikus Jantan (Rattus norvegicus) Galur Wistar Sebagai Model Hiperglikemia - Dhea Nur Fadhilah; Manahan Situmorang; Dumartina Hutahuruk; Julia Susanti (Lembaga Pengembangan Kinerja Dosen, 2023)
Hyperglycemia occurs when the body's condition is too much blood glucose that exceeds normal limits in the body because the body does not produce insulin properly. Betel leaves and ginger rhizomes have long been used by the people in Indonesia as traditional medicines that are believed to reduce blood glucose levels. This study aims to determine the effectiveness of betel leaves and ginger rhizomes empirically to reduce blood glucose levels in hyperglycemia male rats. Betel leaves and rhizomes of ginger are made in the form of infusions and used on 30 heads of hyperglycemia mice divided into 6 groups. Normal group, negative group induced alloxane, positive group (glibenklamide), betel leaf infusion group, ginger rhizome infusion group, betel leaf infusion combination group and ginger rhizome infusion, testing was carried out for 30 days. Data were analyzed with IBM SPSS 20.0 ANOVA and post hoc tukey HSD assays. The results showed that betel leaf infusion at a dose of 2 ml / kg BB and ginger rhizome infusion dose of 2ml / kg BB single administration could reduce blood glucose levels while in combination administration it was seen that there was less effective in reducing blood glucose levels in male white rats.